Uncertain citizenship : everyday practices of Bolivian migrants in Chile - Ryburn, Megan (University of California Press, 2018)
"Uncertain Citizenship explores how Bolivian migrants to Chile experience citizenship in their daily lives. Intraregional migration is on the rise in Latin America and challenges how citizenship in the region is understood and experienced. As Megan Ryburn powerfully argues, many individuals occupy a state of uncertain citizenship as they navigate movement and migration across borders. Drawing on multi-sited ethnographic research, this book contributes to debates on the meaning and practice of citizenship in Latin America and for migrants throughout the world"--Provided by publisher.